Delineation of the Contacts between various formations in the Hit-Kubaiysa area using the 2-D electrical resistivity method - Abd-Allah, Rusul W.; Ali, Kamal K.; AL-Menshed, Firas H. (Iraqi Journal of Science, 2026)
The 2D electrical resistivity method was applied in four selected locations between Hit-Kubaiysa regions, Al- Anbar Governorate, western Iraq. This technique was implemented using the Wenner-Schlumberger array in four survey lines, each line covers 1190m distance. The robust least squares method was used for obtaining the inverted models. The absolute error percentage was less than 0.1%. On the lights of interpretation results, two zones were delineated in the locations of two inverted sections: the first zone represents the Euphrates Formation, while the second zone represents the Dammam Formation. While, in the locations of the other two sections, three zones were found: the first zone represents the Euphrates Formation, the second zone represents the Ana Formation that lies under the Euphrates Formation forming thin beds with a thickness ranging between (10-15 m) approximately, and the third zone represents the Dammam Formation. It is also concluded that the resistivity method is a powerful tool in detecting the contact between the various deposits, even when there is convergence in resistivity contrast if it is applied in a perfect manner theoretically and in the field.